Easymatch- An Eye Localization Method for Frontal Face Images Using Facial Landmarks - Colak, Muhammed Emre; Varol, Asaf (Univ Osijek, Tech Fac, 2020)
Eye detection algorithms are being used in many fields such as camera applications for entertainment and commercial purposes, gaze detection applications, computer-human interaction applications, and eye recognition applications for security, etc. Successful and fast eye detection is an essential step for all these applications in order to achieve good results. There are many eye detection methods in the literature, and most of them rely on the Viola-Jones method to detect the face before localizing eyes. In this paper, a straightforward approach to detect eyes from images which contain a frontal face is proposed. The approach can be used for real-time eye detection using cheap web cameras or other cameras. First, face landmarks are detected from the image, and by utilizing these landmarks; the eye region is determined. The eye radius is estimated by utilizing eye corners. Then, reduced input images are tested with a tailored matching algorithm which does not need image reduction to determine where the eye is.
Keywords: eye localization; face detection; image matching; image processing